The Financial Signaling And Internal Factor Company Against To Earning Per Share - Yudhi Prasetiyo (JAS (Jurnal Akuntansi Syariah))
This research aims to determine the results of financial signal testing as indicated by return on equity (ROE) and liquidity and then the internal company as indicated by company size and audit quality on earnings per share (EPS). The research method used is quantitative. The population of this study is consumer goods companies, totaling 180 companies listed on the Indonesia Stock Exchange (IDX) during 2018-2021. The sample selection technique uses purposive sampling. The data analysis technique uses multiple linear regressions with the IBM SPSS 25 tool. The results show that return on equity, firm size and audit quality affect earnings per share. However, liquidity does not affect earnings per share. This research can be a source of reference for further research. Then it can also be a source of reference for companies in improving financial performance in maintaining the company's existence in the capital market and the maximum consistency of business development to satisfy the principles.